Clinical and Laboratory Characteristics of Children with Chronic Idiopathic Thrombocytopenic Purpura - Milica Cekerevac; Jelena Pantovic; Marija Medovic; Nebojsa Igrutinovic; Sanja Knezevic; Bojana Markovic; Isidora Mihajlovic; Zeljko Todorovic; Tijana Maksic; Natalija Vitosevic; Suzana Zivojinovic; Jelena Cekovic Djordjevic; et al. (Diagnostics)
Background/Objectives: Chronic idiopathic thrombocytopenic purpura (chITP) is an autoimmune disease which develops in 10–30% of patients with newly diagnosed idiopathic thrombocytopenic purpura (ndITP). It is defined as thrombocytopenia which lasts longer than 12 months, with extremely diverse clinical expressions. The aim is to present the most significant clinical and laboratory characteristics of children with chITP. Methods: This is retrospective, observational research, which included children between 2–18 years with chITP who were treated in the Republic of Serbia for 25 years. We analyzed clinical data from personal and family medical histories and different laboratory analyses. Results: The total number of respondents was 152, with female predominance (F:M = 1.27:1) and mild predominance of adolescents. Of the patients, 15% were asymptomatic, but 15% had periodically life-threatening bleeding. Transfusion was not required for 70% of patients. Thirty-five percent of patients had chITP alone, and 45% had high titer levels of autoantibodies. The most frequent comorbidity was Hashimoto thyroiditis (15%). The same percentage (45%) of family members were reported with and without autoimmune diseases. Twenty-five percent of patients were resistant to initial therapy. Helicobacter pylori was detected in 20%, 70% had higher levels of lactate dehydrogenase (LDH), three patients had sufficient serum vitamin D levels, splenomegaly was found in 25%, and accessory spleen in 14% of patients. Around 50% of patients had a platelet count between 20–50 × 10⁹/L, and 40% below 20 × 10⁹/L. Mean platelet volume (MPV) was 10.6 ± 1.4 fL. No dysplastic changes were noted in bone marrow aspirate. Initial first-line therapy was sufficient for 45% of patients, second-line therapy was administered in 25%, splenectomy was performed in 20%, and 10% received all available treatments. Conclusions: The severe clinical form of pediatric chITP is accompanied by a low platelet count, the presence of autoimmune comorbidities, a positive family medical history, resistance to initial therapy, hypovitaminosis D, and rare megakaryocytes in the bone marrow.